Selection and Maintenance of Materialized View Using Genetic Algorithm (International Journal of Engineering and Computer Science, 2018)
Data warehouse is a repository of large amount of data collected from multiple heterogeneous and distributed data sources.  Quick response time and accuracy are the key points for success of any database. Performance of query can be improved by different approaches like query optimization, use of proper data structure etc. But leaving all these alternatives we are planning to use materialized view approach. Materialized views (MV)are   precomputed result of queries. Use of materialized view avoids the visit of data source resulting in the saving the time of query response. In our work we are going to materialize the queries based on their threshold value of accessing the query.